2022
DOI: 10.1093/jas/skac217
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the effects of age, dietary fiber type and level, and injectable antimicrobials on the fecal microbiome and antimicrobial resistance of finisher pigs

Abstract: Age and diet are among the factors that influence the community composition of the fecal microbiome. Additionally, antimicrobial use can alter the composition of bacterial communities. An 86-d study with finisher pigs aimed to evaluate age-related dynamics (d 98-177 of age), effects of types and levels of dietary fiber, and injectable antimicrobials on the fecal microbiome and antimicrobial resistance (AMR) was conducted. A total of 287 pigs, housed in 36 pens, with 7 to 8 pigs per pen, fed a corn grain and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, the association between the Shannon diversity index and age has not been fully clarified. Gaire et al (2022) , postulated that the microbial community in growing pigs becomes more diverse and presumably more stable, with increasing age. Increased diversity is associated with improved robustness of the gut microbiota ( Larsen and Claassen, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between the Shannon diversity index and age has not been fully clarified. Gaire et al (2022) , postulated that the microbial community in growing pigs becomes more diverse and presumably more stable, with increasing age. Increased diversity is associated with improved robustness of the gut microbiota ( Larsen and Claassen, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Streptococcus on the host intestine is less studied than Lactobacillus ( Lan et al, 2023 ). Clostridium sensu stricto , the genus with the second-highest taxon weight in the cluster analysis, is one of the main genus detected in the feces of pigs after weaning ( Chen et al, 2017 ) and its relative abundance increases with age ( Gaire et al, 2022 ). Currently, no study has shown proteolytic capabilities in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, during the early stages of piglet life, the influence of nursing mothers and breed was apparent, but it was the introduction of solid feed and subsequent weaning that predominantly drove the succession of the gut microbiome [ 45 ]. Moreover, diet, age, body weight, and antimicrobial exposure have been established as significant factors shaping the gut microbiome of productions pigs [ 30 , 46 , 47 ]. Additionally, a different investigation emphasized the substantial impact of weaning on the piglet gut microbiome, revealing significant alterations in both bacterial and fungal communities post-weaning [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sugar beet pulp is a rich source of several oligo- and monosaccharides, including mannose, rhamnose, glucuronic and galacturonic acids; glucose; galactose; arabinose; and fucose [ 50 ]. Previous work on pigs demonstrated the minimal effects of SBP supplementation on the commensal gut microbiome [ 51 ], or the selective enrichment of Eubacterium ruminantium in feces following 12 weeks of supplementation [ 52 ]. The effect of SBP on the rumen microbiome of beef calves was negligible [ 53 ]; however, the fecal microbiome of dairy cows revealed the selective enrichment of Fibrobacter sp.…”
Section: Discussionmentioning
confidence: 99%